Sprints, decelerations and turns most commonly precede goals in soccer: analysis of 6 FIFA World Cups - Daly, L.; Caulfield, P.; Martínez-Hernández, D. (European Journal of Sport Science, 2025)
This study investigated actions preceding goals in male and female players across 6 FIFA World Cups. This is the first longitudinal, multi-sex analysis of goal actions using world-class data, extending validity and findings beyond the current evidence base (domestic, single-sex studies). In total, 2995 actions preceding goals from open-play were analysed across the last 6 men's` and women's FIFA world cups (2014-2023) using the modified Bloomfield method. Additionally, possible longitudinal (tournament cycle), sex, and role-based (i.e., scorer vs. assister) differences were examined using Bayesian and chi-squared analyses. Linear advancing movements (˜41%), particularly sprinting, were the most prevalent actions leading to goals, followed by deceleration (˜22%) and turns (˜19%) (Cramer's V = 0.27-0.38; p < 0.05). Longitudinal, between-sex and between-role (i.e., scorer vs. assister) differences were predominantly minimal for movement types (Bayes Factors [BF10] < 0.01; Cramer's V = 0.02-0.06; p > 0.05). Sprinting preceded goals more prevalently for males (43.4%) and scorers (43.2%), when compared with females (39.0%) and assisters (39.1%), respectively (Cramer's V = 0.04-0.10; p < 0.05). Female players performed significantly greater proportions of actions at high intensity versus males (53.0 vs. 47.9%; BF10 = 38.7; Cramer's V = 0.369; p < 0.05), and the 2022/2023 cycle had lower proportion of actions at high intensity compared to earlier cycles (46.6% vs. 52.3%-52.5%; BF10 = 0.019; Cramer's V = 0.06; p < 0.05). This analysis highlights the importance of sprinting, decelerating, and turning for goal-scoring. Therefore, enhancing players' physiological and mechanical reserves to undertake these actions, as and when required during match-play, appears prudent. Further, analysts/coaches may apply this information to identify decisive goal-scoring actions and design targeted training drills accordingly.